الأسس العلمية لتحقيق العدالة في هياكل الأجور الوظيفية - الخير, طارق; المخلافي, عبد الواسع عبد الغني (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث موضوع الأسس العلمية لبناء هياكل الأجور وأهمية اتباعها لتحقيق العدالة في سياسة الأجور والفئات الأجرية. وفيه تم التعرض للأسس الفكرية لبناء هياكل الأجور والمتمثلة في سياسة الأجور وما يجب أن تجسده من مبادئ وتحققه من أهداف منشودة لكل من الموظفين والمنظمة وضرورة تحقيق الواقعية بالاعتماد على نتائج دراسة المتغيرات في البيئة الداخلية والخارجية للنظام الإداري للدولة والتي تؤثر في تحديد مستويات الأجور وكذالك تطرق البحث للطرائق الفنية التي ينبغي اتباعها لتنفيذ سياسة الأجور وتجسيدها في هيكل الأجور من خلال تحديد القيمة النسبية للوظائف وتحديد الخصائص التي ينبغي أن يتصف بها هيكل الأجور. ومن خلاله تم التوصل إلى حقيقة مفادها أن اتباع الأسلوب العلمي في بناء هياكل الأجور من شأنه أن يؤدي الى تحقيق العدالة فى الأجور و يسهم في خلق منظمات إدارية فعالة وكفوءة. This research discusses the subject of the scientific bases of building structures of job wages and the importance of following them in order to do justice in the policy wages and charge categories. It includes the intellectual bases of building the structures of wages represented by the policy it should embody and the principles it should fulfill. It should be realistic in depending on the study of charges in both the internal and external environment. This research also discusses the technical ways which should be followed to fulfill the wages policy through specifying the relative value of jobs and specifying the specifications of the structure of wages. Therefore, the truth was clear that following the scientific way of building the bases of wages leads to justice in the wages and helps in creating competent active administrative organizations.